Resilience, Equity, and Opportunity - World Bank (Washington, DC, 2013)
Risk and the quest for opportunity feature heavily in economic life in the 21st century. Sustained growth in many developing countries has pulled billions out of poverty and into the middle class; but this economic upturn has yet to reach billions more, who face unemployment, disability, or illness, and struggle to protect themselves and their families against shocks. The poor are particularly vulnerable, being typically more exposed to risk and less able to access opportunities. In a world filled with risk and potential, social protection and labor systems are being built, refined or reformed in almost every country to help people and family's find jobs, improve their productivity, cope with shocks, and invest in the health, education, and well-being of their children. The World Bank supports social protection and labor in client countries as a central part of its mission to reduce poverty through sustainable, inclusive growth. The World Bank's new social protection and labor strategy (2012-22) lays out ways to deepen World Bank involvement, capacity, knowledge, and impact in social protection and labor. Three overarching goals, a clear strategic direction, and engagement principles guide this new strategy: 1) the overarching goals of the strategy are to help improve resilience, equity, and opportunity for people in both low- and middle-income countries; 2) the strategic direction is to help developing countries move from fragmented approaches to more harmonized systems for social protection and labor; and 3) the engagement principles for working with clients are to be country-tailored and evidence based in operations and knowledge work, and collaborative across a range of sectors and actors this new strategy addresses gaps in the current practice by helping make social protection and labor more responsive, more productive, and more inclusive of excluded regions and groups notably low-income countries and the very poor, the disabled, those in the informal sector and, in many cases, women. The strategy is not a 'one size fits all' approach. Instead, it calls for improving evidence, building capacity, and sharing knowledge across countries to facilitate informed, country-specific, fiscally sustainable social protection and labor programs and systems. The World Bank will support this agenda not only through lending, but critically by improving evidence, building capacity, and supporting knowledge sharing and collaboration across countries. This social protection and labor strategy builds on the achievements as well as the lessons from practice over the last decade and more. Moreover, it builds on the basic analytical foundation of the first World Bank social protection and labor strategy.